Effects of endurance training on resting and post-exercise cardiac autonomic control - Yamamoto, K.; Miyachi, M.; Saitoh, T.; Yoshioka, A.; Onodera, S. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: Endurance training induces reductions in both resting and postexercise heart rate (HR). If adaptation in cardiac autonomic regulation is a contributing factor in these reductions, changes in cardiac autonomic nervous system (ANS) should correspond to those in HR during an endurance-training program. We investigated the changes in resting and postexercise HR variabilities (both in the time and frequency domain) over a 6-wk training program. METHODS: HR variability was measured five times in an endurance-training group (N = 7) and four times in a control group (N = 5) during the course of study. RESULTS: Endurance training decreased HR and increased indices of parasympathetic modulation measured both at rest and during postexercise recovery periods. Noteworthy is that no changes in either HR or indices of ANS modulation measured during postexercise recovery periods were detectable after the first 7 d of the study despite continued changes in resting HR and indices in ANS modulation measured between the 7th and 42nd days of the endurance-training program. CONCLUSIONS: The study demonstrates that with endurance-training changes in cardiac ANS modulation partly contribute to a decrease in HR at rest and during postexercise recovery period, and that adaptation of the cardiac autonomic control occurs sooner in immediate postexercise periods than at rest.